Optimizing nutrition in pediatric intestinal pseudo‐obstruction syndrome. Issue 5 (10th April 2023) - Pescarin, Matilde; Day, Hannah; Thapar, Nikhil; Jackman, Lucy; Saliakellis, Efstratios; Lindley, Keith J.; Nikaki, Kornilia; Hill, Susan; Kӧglmeier, Jutta; Rybak, Anna; Borrelli, Osvaldo
Abstract: Background: Pediatric intestinal pseudo‐obstruction (PIPO) encompasses a variety of rare, heterogeneous, and disabling disorders that severely affect gastrointestinal motility and are associated with high morbidity and mortality. PIPO management is complex and focuses on maintaining an optimal nutritional status, improving gut function, relieving symptoms, and treating complications. Nutritional issues prevail, and PIPO patients often experience severe undernutrition and faltering growth. Thus, nutritional management plays a pivotal role for achieving the most favorable clinical outcomes. The calorie and nutrient intake of each patient needs to be tailored to age, extent and severity of gut involvement and nutritional needs to support an optimal nutritional status. After defining the extent and severity of gut dysmotility, an experienced team should perform a careful nutritional assessment. An oral diet should always be encouraged and might include bite and dissolve solids, liquid diet or simple oral stimulation. If oral caloric intake is inadequate, liquid gastric feeds should provide the subsequent step. In the presence of severe gastric dysmotility, continuous post‐pyloric feeding represents a viable option. In the most severe cases, parenteral nutrition (PN) is required to meet appropriate nutritional requirements. Purpose: Pediatric data on this topic are scarce and mainly extrapolated from adult studies. In this review, we discuss current evidence and knowledge regarding nutritional options, implications of the use of different feed types, including a blended diet, and the use of PN. Moreover, based on our experience and the evidence from the literature, we propose a flow chart to guide the nutritional management of PIPO patients. Abstract : A nutritional multidisciplinary management plays a pivotal role in achieving the most favorable clinical outcome in children with pediatric intestinal pseudo‐obstruction (PIPO). The current knowledge regarding the nutritional options has been discussed, and a nutritional flow chart to guide the nutritional management of PIPO patients has been suggested.